The impact of past and present energy, macronutrient and micronutrient intake on the incidence of dental caries among 5-year-old urban black South African children - Mackeown, Jennifer Margaret (My University, 2014)
There is a general agreement that food habits change over time. This has been clearly shown in studies conducted in first world countries, but until recently this information has been lacking in South Africa, particularly among preschool children, although nutrition information is available on dietary intake at a particular point of time in some groups. Changing food habits may affect disease. With the rapidly changing socio-political situation in South Africa diet too must have changed and one cannot rely on previous nutritional information. New reliable information is needed to help plan future health needs of all South Africans. Dietary intake in association with dental health has been studied by numerous investigators. Regarding energy and specific nutrients, studies have thus far shown no relationship of energy to dental caries incidence; carbohydrate, particularly sugars, have shown both positive and negative relationships to caries incidence and indirectly dietary fats may be associated with low caries because fat and sugar intake are inversely proportional to each other. The role of trace elements has varied from caries promoting to cariostatic. It is clear though that because of the complex nature of the caries process, carbohydrate intake, together with other macro- and micronutrients, does not fully explain the development of this disease. This could be influenced by the fact that most of the studies conducted on diet and dental health have been cross-sectional. The Vipeholm study in Sweden, the Hopewood House study in Australia and more recently the Michigan study in the United States are the only longitudinal studies that have examined the association between diet and dental caries incidence and both the Vipeholm and Hopewood House studied only selected groups in institutions. Until now no true longitudinal study had been conducted among South African preschool children regarding the association between diet and the development of dental caries. The Birth-to-Ten study is the first such longitudinal study that selected a random sample representative of the population groups in the country and has provided unique information on the longitudinal dietary intake together with the dental health at 1- and 5- years. In addition no South African study has looked at the impact of past diet on the present dental health of the same South African children and the Birth-to-Ten study provided this opportunity.
Keywords: Dental Caries--in infancy & childhood; Diet, Cariogenic--in infancy & childhood